Cutaneous and periodontal inputs to the cerebellum of the naked mole-rat (Heterocephalus glaber) - Sarko, Diana K.; Leitch, Duncan B.; Catania, Kenneth C. (Frontiers in Neuroanatomy, 2013)
The naked mole-rat (Heterocephalus glaber) is a small fossorial rodent with specialized dentition that is reflected by the large cortical area dedicated to representation of the prominent incisors. Due to naked mole-rats’ behavioral reliance on the incisors for digging and for manipulating objects, as well as their ability to move the lower incisors independently, we hypothesized that expanded somatosensory representations of the incisors would be present within the cerebellum in order to accommodate a greater degree of proprioceptive, cutaneous, and periodontal input. Multiunit electrophysiological recordings targeting the ansiform lobule were used to investigate tactile inputs from receptive fields on the entire body with a focus on the incisors. Similar to other rodents, a fractured somatotopy appeared to be present with discrete representations of the same receptive fields repeated within each folium of the cerebellum. These findings confirm the presence of somatosensory inputs to a large area of the naked mole-rat cerebellum with particularly extensive representations of the lower incisors and mystacial vibrissae. We speculate that these extensive inputs facilitate processing of tactile cues as part of a sensorimotor integration network that optimizes how sensory stimuli are acquired through active exploration and in turn adjusts motor outputs (such as independent movement of the lower incisors). These results highlight the diverse sensory specializations and corresponding brain organizational schemes that have evolved in different mammals to facilitate exploration of and interaction with their environment.